SOLUTION: 6x - 3(y + 7) = 3 10x = y + 7 I don't know how to get this started. All I end up with are two different variables and 1 actual number. Please help

Algebra ->  Algebra  -> Expressions-with-variables -> SOLUTION: 6x - 3(y + 7) = 3 10x = y + 7 I don't know how to get this started. All I end up with are two different variables and 1 actual number. Please help      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Expressions involving variables, substitution Solvers Lessons Answers archive Quiz In Depth

 Question 182273This question is from textbook Elementary and Intermediate Algebra : 6x - 3(y + 7) = 3 10x = y + 7 I don't know how to get this started. All I end up with are two different variables and 1 actual number. Please helpThis question is from textbook Elementary and Intermediate Algebra Found 2 solutions by Alan3354, solver91311:Answer by Alan3354(30993)   (Show Source): You can put this solution on YOUR website!6x - 3(y + 7) = 3 --> 6x - 3y - 21 = 3 --> 2x - y - 7 = 1 2x - y = 8 eqn 1 10x = y + 7 eqn 2 Solve for y in eqn 2 y = 10x - 7 Sub for y into eqn 1 2x -(10x-7) = 8 2x-10x+7 = 8 -8x = 1 x = -1/8 ------------ y = 10x-7 y = -5/4 - 7 y = -33/4 Answer by solver91311(16877)   (Show Source): You can put this solution on YOUR website! Put them both in standard form, namely Multiply equation (2) by -3: Add Eq (3) to Eq (1): Substitute into Eq (1) I'll let you do the arithmetic to determine the value of y. John